Assessment of efficiency and safety of adenovirus mediated gene transfer into normal and damaged murine livers. Issue 4 (1st October 2000) - Nakatani, T; Kuriyama, S; Tominaga, K; Tsujimoto, T; Mitoro, A; Yamazaki, M; Tsujinoue, H; Yoshiji, H; Nagao, S; Fukui, H
Abstract : BACKGROUND: When recombinant adenoviruses are infused directly into the circulation, transgene expression is almost completely restricted to the liver. AIMS: Efficiency and safety of adenovirus mediated gene transfer into damaged livers were examined in mice with liver cirrhosis or fulminant hepatitis. METHODS: Liver cirrhosis and fulminant hepatitis were induced by intraperitoneal administration of thioacetamide and d -galactosamine followed by lipopolysaccharide, respectively. Mice were infused with adenoviruses carrying the Escherichia coli β-galactosidase gene, lacZ gene, into the tail vein. Transduction efficiency of the lacZ gene was estimated histochemically by X-gal staining and quantitatively using a chemiluminescent assay. Activation of adenovirus specific T cells and development of neutralising antibodies against adenovirus were also examined. RESULTS: Histochemical evaluation revealed that approximately 40%, 80%, and 40% of cells in normal, cirrhotic, and fulminant hepatitis livers, respectively, were stained blue using X-gal staining. Quantitative analyses revealed that levels of lacZ expression in cirrhotic livers were approximately 2.5-fold and sixfold greater than those in normal and fulminant hepatitis livers, respectively. Although transgene expression in fulminant hepatitis livers was significantly lower than that in normal livers, marked levels of transgene expression were achieved even in fulminant hepatitis livers. Significant adverse effects of adenoviruses were not observed in damaged livers. There were no significant differences in cellular or humoral immune responses to adenoviruses among animals with normal, cirrhotic, and fulminant hepatitis livers. CONCLUSIONS: Our results suggest that gene therapy with adenoviruses may be used efficiently and safely, even in patients with severe liver disease.